Gambaran Tingkat Pengetahuan Dan KecemasanPada Penderita Tb Paru Yang Menjalani Pengobatan Di Ruang Pojok Tb Rumah Sakit Dr. R. Soeprapto Cepu - Fridayani, Arni; Fahrun Nur Rosyid, Fahrun Nur Rosyid S.Kep, M.Kes (2017)
Tuberculosis is a disease caused by mycrobacterium erculosis in pulmonary of human organ. Tuberculosis has become one of the leading causes of death in the world and to this day remains a global health problem. Indonesia in particular has made effot to all eviate pulmonary TB disease prevalent in various regions with the examination and treatment free of charge. Pulmonary TB disease progression in patient caused by several factors that include anxiety as well as knowledge of Pulmonary TB disease on patient and families. The purpose of this study was to get a description of the level of anxiety as well as knowledge of the Tuberculosis patient who under went treatment in Tuberculosis Corner of Dr. R. Soeprapto Cepu hospital. The method that used is escriptive of case study, the population of tuberculosis patients who come to the Tuberculosis Corner of Dr. R. Soepapto hospital, sampling using the accidental sampling technique and total sample is obtained 71 person. Data analysist technique using qualitative data analysis. The result showed that the pulmonary tuberculosis patients who has mild anxietyare 52 person (73,2%), patients with moderate anxiety are 13 person (18,3%), patient who do not has anxiety were 6 person (8,5%), and no patients has high anxiety. For the knowledge analysis of pulmonary tuberculosis there patient have a good knowledge of tuberculosis disease they are 42 person (59,2%), and patients who have a moderate knowledge of tuberculosis disease are 24 person (40,8%), and none of the patient who have low knowledge about pulmonary tuberculosis disease. Keyword : Pulmonary Tubreculosis, Anxiety, Knowledge